Video how right breastfeeding through smartphone can affect breasfeeding self efficacy on public mothers in the Regency of Banjarnegara - Dian Nirmala Sari; Umi Nur Fajri (Alma Ata University Press, 2022)
Background: The lower confidence of mothers to breastfeed can have an impact on inadequate breastfeeding and can cause nutritional deficiencies in infants so that babies are vulnerable to disease, especially newborns. With increasing mother's confidence in breastfeeding, intervention is needed, one of which is through videos on how to breastfeed correctly. The low level of mother's self-efficacy or mother's belief in breastfeeding illustrates that there is still low commitment to breastfeeding, low endurance of mothers in overcoming obstacles that arise during breastfeeding and mother's focus on negative aspects of breastfeeding so that it has an impact on inadequate breastfeeding and can lead to deficiency. nutrition in infants so that infants are susceptible to disease.The magnitude of the influence of mother's belief in breastfeeding requires various interventions to increase this belief so that success in breastfeeding is achieved. One of the interventions given to increase confidence is to provide videos on how to breastfeed correctly.Objectives: The goal is to find out which breastfeeding video media have an effect on breastfeeding self-efficacy. Methods: The research design used was a quasi-experimental design with a pretest post-test control group design. The variables in this study were videos on how to breastfeed correctly, breastfeeding self-efficacy. The number of samples is 30 respondents. The treatment group received the intervention to get video education on correct breastfeeding techniques using an application on a smartphone, while the control group received education from maternal and child health books. Data analysis was univariate, bivariate with paired t and unpaired t. Results: The results of the analysis show that there is an effect of the video on how to properly breastfeed the effect on the breastfeeding self efficacy p value 0.003Conclusions: Giving videos on how to breastfeed correctly can increase the confidence of mothers to breastfeed their babies.